Guidelines for evaluating the conservation value of African lion (Panthera leo) translocations - Becker, Matthew S.; Almeida, Joao; Begg, Colleen; Bertola, Laura; Breitenmoser, Christine; Breitenmoser, Urs; Coals, Peter; Funston, Paul; Gaylard, Angela; Groom, Rosemary; Henschel, Philipp; Ikanda, Dennis; et al. (Frontiers in Conservation Science, 2022)
As the top predator in African ecosystems, lions have lost more than 90% of their historical range, and few countries possess strong evidence for stable populations. Translocations (broadly defined here as the capture and movement of lions for various management purposes) have become an increasingly popular action for this species, but the wide array of lion translocation rationales and subsequent conservation challenges stemming from poorly conceived or unsuitable translocations warrants additional standardized evaluation and guidance. At their best, translocations fill a key role in comprehensive strategies aimed at addressing the threats facing lions and fostering the recovery of wild populations in their historic range. At their worst, translocations can distract from addressing the major threats to wild populations and habitats, divert scarce funding from more valuable conservation actions, exacerbate conflict with humans in recipient sites, disrupt local lion demography, and undermine the genetic integrity of wild lion populations in both source and recipient sites. In the interest of developing best practice guidelines for deciding when and how to conduct lion translocations, we discuss factors to consider when determining whether a translocation is of conservation value, introduce a value assessment for translocations, and provide a decision matrix to assist practitioners in improving the positive and reducing the negative outcomes of lion translocation.